PORTFOLIO RESOURCE ALLOCATION IN CUSTOMER VALUE DELIVERY PROJECTS: Dynamic Capability and organizational Learning Perspective - Butt, Aurangzeab (My University, 2012)
Resources characterize the value creation potential of an organization. Management of organizational resource is an outcome of structuring, bundling and leveraging processes. Organizations integrate, enhance and alter their existing resource combination by deploying the dynamic capabilities. Cognitive learning processes of experience accumulation, knowledge articulation and knowledge codification are instrumental for the dynamic capability evolution. Management of resources is imperative to realize the Project Portfolio Management accomplishment as well. However the allocation and balancing of the resources among the project portfolio members is rarely addressed in the literature. With constructivism approach this study emphasizes the project portfolio resource allocation dilemma and its resolution in dynamic capabilities and organizational learning perspective.The research concludes with a pragmatic proposal to develop portfolio resource allocation dynamic capability in the case organization. It was further realized that the observed learning mechanisms in the case organization will underpin the development and strengthen the PPM dynamic capabilities.
Keywords: Resource management; Dynamic Capabilities; Organizational Learning; Project Portfolio Management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|